Relación entre la gestión del presupuesto por resultados y la calidad del gasto en los gobiernos locales de la región La Libertad al 2015 - Vargas Merino, Jorge Alberto (2017)
ABSTRACT This investigation searched to analyse the relationship between the Budget Management by Results and the quality of the expenditure of the local governments from La Libertad Region up to 2015. It was non-experimental, longitudinal and predictive correlational, worked with the 83 local governments from La Libertad Region, and the content analysis was used as a research technique. The diagnosis of the Budget Management by Results, shows a level of execution at 84% in the region, while in the 83 districts, execution reaches 66%. On the other hand, at function level, the Environment Function, occupies the first place with 78%. The main source of funding for the budgetary programs in the years 2012-2015 are determined resources. The quality of the expenditure was measured, identifying the indicators that guide the improvement of the living standards of the population, thus the Prevalence of chronic malnutrition in children under 5 years (WHO pattern) indicator, has maintained a downward trend since 2010. To 2015, La Libertad presents a percentage of 15.9%. The indicator of satisfactory level in reading comprehension has been increasing year by year, going from 15.41% in 2008 to 42.52% in 2015; And as for the satisfactory level in mathematics, in 2015, reached 23.23%. A significant growth is observed, although there is still a significant gap. In other budget instruments, progress was identified by the results, as well as, with the DEBS, it concludes that 69 DEBS evaluations have been programmed, of which 52 have been completed by the end of 2015; the others are in the process of implementation. Regarding the Incentive Plan for Municipal Management, the percentage of achievement of goals, for all types of investigadores municipalities is 73%. There is a direct and significant relationship between results-based budget management and quality of expenditure, which is checked first with the level of global significance of the statistical model [Prob (F Statistic) = 0.0000]. It is also contrasted with the correlation coefficient of 0.69, mainly with indicators of Urban and Rural Sanitation Programs, the Program of Access and Adequate Use of Telecommunications Services, and the EBR Learning Achievement Program.